(untitled) (Oxford, 1989)
This book provides intensive extra practice and includes exercises in writing, pronunciation, vocabulary and multi-word verbs, dependent prepositions and linking words
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc